MENGEMBANGKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS MELALUI DISCOVERY LEARNING BERBASIS SCIENTIFIC APPROACH - Purwaningrum, Jayanti Putri (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
Mathematical creative thinking ability is one of the capabilities that need to be owned anddeveloped in students who study mathematics from primary to university level. This is due to thoseabilities in accordance with the vision of mathematics, national education goals and learningobjectives of the school mathematics. This paper is a contribution of new ideas for implementingthe curriculum in education so as to develop mathematical creative thinking ability in school.Information about mathematical creative thinking ability derived based on a literature review. Thestudy results are expected that mathematical creative thinking ability can progress throughdiscovery learning based scientific approach.